Intravascular Laser Irradiation of Blood (ILIB) modificado no processo de cicatrização de úlcera em pé diabético: ensaio clínico randomizado - BLASCOVICH, Hellyangela Bertalha (2023)
Diabetic foot ulcers are a worldwide public health problem, and may lead to lower limb amputation, due to impairments in the healing process caused by factors such as prolonged inflammation and oxidative stress. Thus, the Intravascular Laser Irradiation of Blood (ILIB) appears as a therapeutic possibility due to its anti-inflammatory and antioxidant action. Therefore, the objective was to evaluate the effectiveness of the photobiomodulatory action of the modified Intravascular Laser Irradiation of Blood (ILIB) in the healing process of ulcers in patients with diabetic foot. This is a randomized, controlled, uni-blind clinical trial, developed in a single center at the Diabetic Foot outpatient clinic at Hospital Municipal de Imperatriz. The sample consisted of 14 participants, equally distributed, randomly, into two groups: control group (CG), which used standard treatment at the study site, and experimental group (GILIB), which associated the application of modified ILIB to standard treatment, with 100mW power, 660nm wavelength, with 10 applications in total. Sociodemographic and clinical data, photographic records of the ulcers and assessment of the area, depth measurement and analysis of the clinical aspects of the ulcers were collected with the help of 14 nursing outcome indicators (NOC) Wound healing: secondary intention. This information was collected in three moments (D1, D5, D12) of the study protocol that lasted 12 consecutive days. Hematological and biochemical analyzes were performed at baseline (D1) and end of the study (D12). Data were statistically analyzed with a confidence interval of 95% and a significance level of 5% (p ≤ 0.05). Study approved by the Ethics and Research Committee on Human Beings (n°5,219,607) with the Brazilian Registry of Clinical Trials (RBR-3v7mrsq). The sample, in both groups, showed a predominance of males, brown race, with low education, aged between 56 and 60 years. The mean time for the appearance of the ulcer in the GILIB was 12 (±8.0) months and 7.7 (±7.3) months in the CG, located mainly on the plantar surface, and classified predominantly as grade 1 and stage A (University of Texas ranking) in both groups. There was a reduction in the mean area of the ulcer in the GILIB, in the intragroup analysis (p=0.02), while in the CG there was an increase in the mean area of the ulcer (p=0.23). The NOC indicators with the best results in the GILIB tissue repair process were Erythema in the skin around the lesion (p=<0.001), Wound inflammation (p=<0.001), Edema around the lesion (p=0.05), Macerated skin (p=<0.001), while in the CG, detachment under the wound edges (p=0.03) and unpleasant odor in the wound (p=0.01) stood out. The granulation indicator obtained a significant difference between the groups, however, without observing improvement in both. The other indicators showed no significant difference between the groups. As for the hematological and biochemical parameters, in GILIB there was an increase in rods, neutrophils and a reduction in platelets and LDL, statistically significant in relation to the CG. It is concluded, therefore, that the modified ILIB applied to individuals with diabetic foot ulcer promoted a reduction in the total area of the ulcer, alterations in the clinical indicators of NOC and hematological and biochemical alterations.